Responsive and Modern Look - Felczak, Michael (PKP Barcelona 2019 Workshop, 2019)
Clean and spacious layout Adapt to readers: mobile, tablet, and desktop support Support for multiple article formats: PDF, HTML, XML, EPUB, AUDIO, VIDEO Free themes available to all journals Customizable to reflect journal identity Expand the look and consumption of academic content Visually attractive Audio, video, data sets as supplementary content Support diverse reader access across devices